Pretreatment of food waste for sugars and biogas production via microwave irradiation - Ong, Yen Peng (2014)
Food waste quantities have escalated over the years, especially in the developed parts of the world. As a result of this increasing trend, many countries have faced problems with the disposal of food waste, such as rising cost of incineration, depleted landfill areas and air and land pollution. Therefore in this study, a form of promising technology which allows for the conversion of food waste into sugars and biogas production through anaerobic digestion (via microwave irradiation) is tried and analysed.